ANALYSIS OF THE EFFECT OF INFLATION, EXPORTS AND IMPORTS ON INDONESIA'S ECONOMIC GROWTH - Gabriella Millenia Stievany; Gentur Jalunggono (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
Economic growth is defined as an increase in GDP or GNP regardless of whether the increase is larger or less than the rate of population growth, and whether or not there is a change in the structure of the economy. This study attempts to determine the effect of exports, capital formation, and government spending on Indonesia's economic growth. This research method takes a quantitative approach. The data collected is secondary data obtained from the World Bank in the form of time series from 1989 to 2018. The data analysis technique employs time series data analysis with the ECM (Error Correction Model) model with the help of Eviews software. The results reveal that exports and imports have a considerable effect in the short and long term on economic growth, but inflation has no significant effect in the short and long term on economic growth.